The bald bandit - Roy, Ron, 1940-; Gurney, John Steven, 1962- (New York : Scholastic, 1997)
Third-grader Dink and his detective friends hope to receive a big reward by finding the person whose video recorder picked up a picture of the local bank robber.
K
"A stepping stone book."
"B"--Spine.
b
K
Keywords: Mystery and detective stories